2002
DOI: 10.1073/pnas.262655099
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mouse clonogenic megakaryocyte progenitors

Abstract: Although it has been shown that unfractionated bone marrow, hematopoietic stem cells, common myeloid progenitors, and bipotent megakaryocyte͞erythrocyte progenitors can give rise to megakaryocyte colonies in culture, monopotent megakaryocyte-committed progenitors (MKP) have never been prospectively isolated from the bone marrow of adult mice. Here, we use a monoclonal antibody to the megakaryocyte-associated surface protein, CD9, to purify MKPs from the c-kit ؉ Sca-1 ؊ IL7R␣ ؊ Thy1.1 ؊ Lin ؊ fraction of adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
137
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(147 citation statements)
references
References 37 publications
10
137
0
Order By: Relevance
“…21 In 2 independent experiments, we found no differences in CFU-S 12 colony numbers between Asxl1 mutant and control samples within either experiment (data not shown).…”
Section: Effects Of Asxl1 Tm1bc Mutation On Progenitor and Hematopoiementioning
confidence: 77%
“…21 In 2 independent experiments, we found no differences in CFU-S 12 colony numbers between Asxl1 mutant and control samples within either experiment (data not shown).…”
Section: Effects Of Asxl1 Tm1bc Mutation On Progenitor and Hematopoiementioning
confidence: 77%
“…In the myeloid branch, CMPs gave rise to 2 more restricted progenitors, megakaryocyte-erythrocyte progenitors (MEPs) and granulocyte-macrophage progenitors (GMPs), 5 with MEPs giving rise to erythroid progenitors and unipotent megakaryocytic precursors ( Figure 1A). 8,9,28 Although the classical model of hematopoiesis is simple in its binary conception of lineage potential, this model of hematopoiesis has been challenged by the identification of new progenitor populations. On the basis of their prior observation that loss of long-term HSC (LT-HSC) self-renewal coincided with the upregulation of FMS-like tyrosine kinase 3 (Flt3) 29 32 Because megakaryocytes and erythrocytes were thought to share a common progenitor, 5 the authors investigated the erythroid potential of LSKFlt3 1 cells and showed that these cells also exhibited limited ability to form erythroid progeny at a clonal level.…”
Section: Recently Wilson Et Almentioning
confidence: 99%
“…[5][6][7] Moreover, unipotent megakaryocytic progenitor cells were placed downstream of bipotent MegE progenitors, suggesting that all megakaryocytes arise from committed precursors that are formed after requisite intermediate states. 8,9 Although the hierarchical model has been very useful for understanding hematopoiesis, it has become increasingly clear that this model is inadequate for capturing all the complexities of early commitment steps in hematopoiesis and especially in megakaryopoiesis. With advances in the ability to prospectively separate HSCs and committed progenitors and the development of functional and molecular assays to assess the development potential of single cells in vitro and in vivo, a more complex picture of HSC commitment to the megakaryocytic lineage has emerged in which megakaryocytes may arise directly from HSCs as well as from multi-, bi-, and unipotent progenitors.…”
Section: Introductionmentioning
confidence: 99%
“…To address whether we could also observe the same results from a definitive erythroid source, we developed a protocol to prospectively sort dispersed cells from differentiating EBs at day 6 (and thus enriched for definitive erythroid cell production) into lin-Kit+sca1- Akashi et al, 2000;Nakorn et al, 2003;Terszowski et al, 2005), and plated these individually sorted cells at low density onto methylcellulose under conditions optimal for definitive colony analysis. It has been difficult to obtain colonies from such prospectively sorted populations when derived from differentiating EBs (Drissen et al, 2010); indeed, we found that use of an ESC-based medium rather than the standard media conditions was absolutely crucial for success (see Materials and Methods).…”
Section: Erythroblastic Islands From Differentiating Embryonic Stem Cmentioning
confidence: 99%